2010
DOI: 10.1029/2009wr007702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for estimating the effects of vegetation change and climate variability on streamflow

Abstract: [1] Changes in vegetation cover can significantly affect streamflow. Two common methods for estimating vegetation effects on streamflow are the paired catchment method and the time trend analysis technique. In this study, the performance of these methods is evaluated using data from paired catchments in Australia, New Zealand, and South Africa. Results show that these methods generally yield consistent estimates of the vegetation effect, and most of the observed streamflow changes are attributable to vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
142
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 43 publications
4
142
0
2
Order By: Relevance
“…However, such an experimental approach is not suitable for large watersheds simply because of the difficulty in locating a comparable control watershed for an impacted watershed. In order to overcome this methodological challenge, various approaches have been explored, including hydrological modeling (Tuteja et al, 2007), statistical analysis (Wei and Zhang, 2010;Zhao et al, 2010), sensitivity tests (Milly and Dunne, 2002) and trend analysis (Wilcox and Huang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, such an experimental approach is not suitable for large watersheds simply because of the difficulty in locating a comparable control watershed for an impacted watershed. In order to overcome this methodological challenge, various approaches have been explored, including hydrological modeling (Tuteja et al, 2007), statistical analysis (Wei and Zhang, 2010;Zhao et al, 2010), sensitivity tests (Milly and Dunne, 2002) and trend analysis (Wilcox and Huang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest challenge is how to separate their relative contributions to hydrology (Zhang et al, 2008;Wang et al, 2009;Zheng et al, 2009;Wei and Zhang, 2010b). Physically-based hydrological modeling is commonly used to assess the relative effects of climate variability and forest change on hydrology (Tuteja et al, 2007;Juckem et al, 2008;Zégre et al, 2010;Zhao et al, 2010). However, this modeling approach is only suitable for the watersheds that are well monitored with extensive, longterm data available on vegetation, soil, topography, land use, hydrology and climate (Wei and Zhang, 2010a, b).…”
mentioning
confidence: 99%
“…One of the key components of FCFC is the method of Zhang et al (2001) for estimating differences in mean annual streamflow under different degrees of forest cover. The method of Zhang et al (2001) has been widely used (Jackson et al, 2005;Sun et al, 2006) and a number of studies tested its accuracy using data from experimental catchments (Brown et al, 2005;Zhao et al, 2010). Brown et al (2005) compared estimated changes in mean annual streamflow using the method of Zhang et al (2001) with those observed from paired catchment studies, and showed that the method of Zhang et al (2001) yielded good estimates of the changes in mean annual streamflow from catchments involving conifer and eucalyptus.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (2005) compared estimated changes in mean annual streamflow using the method of Zhang et al (2001) with those observed from paired catchment studies, and showed that the method of Zhang et al (2001) yielded good estimates of the changes in mean annual streamflow from catchments involving conifer and eucalyptus. Zhao et al (2010) evaluated methods for estimating the effects of vegetation cover change on streamflow using paired catchment data from Australia, New Zealand, and South Africa. The study showed that the method of Zhang et al (2001) provided consistent estimates of vegetation impact on mean annual streamflow compared with paired catchment method and time-trend analysis method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation